Modified high-nickel ternary positive electrode material, preparation method and application thereof

CN115602810BActive Publication Date: 2026-10-30SHANDONG AIA KESIMAO NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211204957.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-29
Publication Date
2026-10-30
Estimated Expiration
2042-09-29

AI Technical Summary

Technical Problem

但聚合物包覆层由于其反应的独特性,很难控制包覆层厚度,常常维持在20~30nm水平,不利于电极的活性物质容量占比,并且部分聚合物包覆层难以达到材料、制备的经济性

Benefits of technology

[0016]通过上述技术方案,本公开提供的改性高镍三元正极材料的表面具有丙烯酸类单体和含氟丙烯酸类单体共聚形成的共聚物包覆层,其中共聚物中的羟基可以与高镍三元正极材料表面的锂残留化合物发生反应,生成可导电的聚合物,避免循环过程中锂残留加剧气体的释放,减少运行过程中电池破裂的风险;同时氟离子具有弱酸性,可以中和锂残留化合物水解出来的强碱性氢氧根离子,避免氢氧根离子与浆料中的含氟粘合剂反应、使粘合剂脱氟生成氟化衍生物,从而减少氟化衍生物的量,避免氟化衍生物对正极材料侵蚀;此外氟离子还具有疏水性,可抑制环境中的水与正极材料表面接触,使高反应活性的正极材料与电解液隔绝,起到物理保护的作用。本公开提供的改性高镍三元正极材料具有稳定的层状结构、良好的循环稳定性及倍率性能,用于电池中时可显著提高电池在高温高压下的循环稳定性及倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115602810B_ABST
    Figure CN115602810B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a modified high-nickel ternary positive electrode material, a preparation method and application thereof, the modified high-nickel ternary positive electrode material comprising a high-nickel ternary positive electrode material and a copolymer coating layer coated on the surface of the high-nickel ternary positive electrode material, the copolymer coating layer being formed by copolymerization of an acrylic monomer and a fluorine-containing acrylic monomer; the number average molecular weight of the copolymer in the copolymer coating layer being 1200-20000 g / mol, and the thickness of the copolymer coating layer being 1-20 nm. The modified high-nickel ternary positive electrode material provided by the present disclosure has a stable layered structure, good cycle stability and rate performance, and can significantly improve the cycle stability and rate performance of the battery under high temperature and high pressure when used in the battery. The modified high-nickel ternary positive electrode material provided by the present disclosure has a stable layered structure, good cycle stability and rate performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of lithium-ion battery materials, specifically to a modified high-nickel ternary cathode material, its preparation method, and its application. Background Technology

[0002] High-nickel ternary cathode material (LiNi) x Co y Mn 1-x-y O2 (x>0.5) has become a research hotspot for power battery cathode materials due to its advantages such as high discharge specific capacity, low cost, and environmental friendliness. However, as the nickel content increases, the surface properties of the material become more unstable. Residual lithium on the surface of high-nickel ternary cathode materials exposed to air easily forms impurity phases such as Li2CO3 and LiOH, increasing the alkalinity of the material particles. This not only makes subsequent coating processes difficult, but the insulating impurity phases also increase the interfacial impedance of the material. In addition, during deeper delithiation, the high-valence transition metal ions on the particle surface have strong oxidizing properties and easily react with the electrolyte, causing capacity loss. Finally, repeated electrochemical reactions can induce degradation of the surface structure of high-nickel ternary cathode materials, deteriorating electrochemical performance and thus limiting their widespread application. Surface coating is widely used for the modification of high-nickel ternary cathode materials because the coating layer can, on the one hand, inhibit the irreversible phase transition and dissolution of transition metal ions in the high-nickel ternary cathode material during charge and discharge, and on the other hand, reduce the direct contact between the material and the electrolyte, reducing the occurrence of side reactions, thereby maintaining the structural stability of the cathode during cycling. Common coating materials include inorganic and organic coatings. Inorganic coating involves coating the surface of a ternary cathode with a modified material in an inorganic system. In an inorganic coating tank, the ternary cathode and pure water are placed in a specific ratio. After stirring to uniformly disperse the ternary cathode particles in the water, the coating material is slowly added under suitable temperature and pH conditions to uniformly coat the ternary cathode surface. However, it is difficult to control the formation of a uniform and soft coating surface layer, and the particles are brittle, still prone to structural breakage due to stress after multiple cycles. Organic coating, on the other hand, coats the ternary cathode in an organic system, resulting in better uniformity than inorganic coatings. Currently, most reports utilize conductive polymers such as polyaniline, polypyrrole, and polyvinylpyrrolidone, combined with one or more complementary metal oxides or lithium residue scavengers for modification. The good ductility and flexibility of organic coatings lead to breakthroughs in mechanical properties and bifunctional conductivity, thereby improving rate performance. However, due to the unique nature of the polymer coating, it is difficult to control the coating thickness, which is often maintained at the 20-30 nm level. This is not conducive to the proportion of active material capacity in the electrode, and some polymer coatings are difficult to achieve the economic efficiency of materials and preparation. Summary of the Invention

[0003] The purpose of this disclosure is to provide a modified high-nickel ternary cathode material, its preparation method and application. The modified high-nickel ternary cathode material has a stable layered structure, good cycle stability and rate performance. When used in batteries, it can significantly improve the cycle stability and rate performance of batteries under high temperature and high pressure.

[0004] To achieve the above objectives, the first aspect of this disclosure provides a modified high-nickel ternary cathode material, the modified high-nickel ternary cathode material comprising a high-nickel ternary cathode material and a copolymer coating layer covering the surface of the high-nickel ternary cathode material, the copolymer coating layer being formed by copolymerization of acrylic monomers and fluorinated acrylic monomers; the number average molecular weight of the copolymer in the copolymer coating layer being 1200-20000 g / mol, and the thickness of the copolymer coating layer being 1-20 nm.

[0005] Optionally, the acrylic monomers include one or more of acrylic acid, methacrylic acid, methyl acrylate, n-butyl acrylate, methyl methacrylate, and benzyl methacrylate; the fluorinated acrylic monomers include one or more of trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate, and hexafluorobutyl methacrylate.

[0006] Optionally, the copolymer exists in the form of copolymer particles; the chemical formula of the high-nickel ternary cathode material is shown in formula (I): LiNi x Co y M z O2(I), where 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M includes Mn and Al.

[0007] A second aspect of this disclosure provides a method for preparing the modified high-nickel ternary cathode material described in the first aspect of this disclosure, the method comprising the following steps:

[0008] (1) Acrylic monomers and fluorinated acrylic monomers are copolymerized in the presence of an initiator and a first solvent to obtain a first material; a precipitant is added to the first material to obtain copolymer particles;

[0009] (2) Mix and stir the copolymer particles, high-nickel ternary cathode material and second solvent, and spray dry the resulting second material.

[0010] Optionally, in step (1), the molar ratio of the acrylic monomer to the fluorinated acrylic monomer is (0.05-3):1, preferably (0.2-0.6):1; based on the weight of the first solvent, the total content of the acrylic monomer and the fluorinated acrylic monomer is 15-50% by weight.

[0011] Optionally, in step (1), the content of the initiator is 0.01 to 4% by weight, based on the weight of the first solvent; the volume ratio of the first material to the precipitant is (0.01 to 2): 1; the temperature of the copolymerization reaction is 70 to 90°C, and the time is 0.5 to 10 h.

[0012] Optionally, the initiator includes one or more of peroxide initiators, azo initiators, and redox initiators; preferably, the initiator includes one or more of benzoyl peroxide tert-butyl ester, benzoyl peroxide, methyl ethyl ketone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, ammonium persulfate, and benzoyl peroxide; the precipitant includes one or more of dimethyl diacetone oxime, 8-hydroxyquinoline, sodium tetraphenylborate, and methanol; the first solvent includes one or more of dioxane, isopropanol, acetone, chloroform, and propylene oxide; the second solvent includes one or more of dioxane, isopropanol, acetone, ethanol, and ethyl acetate.

[0013] Optionally, in step (2), the weight ratio of the copolymer particles to the high-nickel ternary cathode material is (0.01-40):100.

[0014] Optionally, in step (2), the conditions for spray drying include: drying the second material by passing it through a centrifugal spray dryer, wherein the inlet air temperature of the centrifugal spray dryer is 150-300°C, the outlet air temperature is 50-100°C, and the rotation speed of the spray disc is 10000-20000 r / min; wherein the solid content of the second material is 10-80%.

[0015] The third aspect of this disclosure provides an application of the modified high-nickel ternary cathode material described in the first aspect of this disclosure in batteries.

[0016] Through the above technical solution, the modified high-nickel ternary cathode material provided in this disclosure has a copolymer coating layer formed by the copolymerization of acrylic monomers and fluorinated acrylic monomers. The hydroxyl groups in the copolymer can react with residual lithium compounds on the surface of the high-nickel ternary cathode material to generate a conductive polymer, preventing the release of gas due to lithium residue during cycling and reducing the risk of battery rupture during operation. Simultaneously, fluoride ions, being weakly acidic, can neutralize the strongly alkaline hydroxide ions released from the hydrolysis of residual lithium compounds, preventing the hydroxide ions from reacting with the fluorinated binder in the slurry and causing defluorination of the binder to generate fluorinated derivatives, thereby reducing the amount of fluorinated derivatives and preventing their corrosion of the cathode material. Furthermore, fluoride ions are hydrophobic, inhibiting contact between water in the environment and the cathode material surface, isolating the highly reactive cathode material from the electrolyte and providing physical protection. The modified high-nickel ternary cathode material provided in this disclosure has a stable layered structure, good cycle stability and rate performance, and when used in batteries, it can significantly improve the cycle stability and rate performance of the battery under high temperature and high pressure.

[0017] Other features and advantages of this disclosure will be described in detail in the following detailed description section. Attached Figure Description

[0018] The accompanying drawings are provided to further illustrate the present disclosure and form part of the specification. They are used together with the following detailed description to explain the present disclosure, but do not constitute a limitation thereof. In the drawings:

[0019] Figure 1 This is a preparation route diagram of the acrylic acid-trifluoroethyl methacrylate copolymer in one specific embodiment of the modified high-nickel ternary cathode material provided in this disclosure. Detailed Implementation

[0020] The specific embodiments of this disclosure will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit this disclosure.

[0021] The first aspect of this disclosure provides a modified high-nickel ternary cathode material, the modified high-nickel ternary cathode material comprising a high-nickel ternary cathode material and a copolymer coating layer coated on the surface of the high-nickel ternary cathode material, the copolymer coating layer being formed by copolymerization of acrylic monomers and fluorinated acrylic monomers; the number average molecular weight of the copolymer in the copolymer coating layer is 1200-20000 g / mol, and the thickness of the copolymer coating layer is 1-20 nm.

[0022] The modified high-nickel ternary cathode material disclosed herein has a copolymer coating layer formed by copolymerizing acrylic monomers and fluorinated acrylic monomers. Fluoride ions on the copolymer coating layer can react with residual lithium compounds on the surface of the high-nickel ternary cathode material to generate a conductive polymer, preventing the release of gases due to lithium residue during cycling and reducing the risk of battery rupture during operation. Simultaneously, the fluoride ions are weakly acidic, neutralizing the strongly alkaline hydroxide ions released from the hydrolysis of residual lithium compounds, preventing the hydroxide ions from reacting with the fluorinated binder in the slurry and causing defluorination of the binder to generate fluorinated derivatives, thereby reducing the amount of fluorinated derivatives and preventing their corrosion of the cathode material. Furthermore, the fluoride ions are hydrophobic, inhibiting contact between water in the environment and the cathode material surface, isolating the highly reactive cathode material from the electrolyte and providing physical protection. The modified high-nickel ternary cathode material disclosed herein possesses a stable layered structure, good cycle stability and rate performance, and when used in batteries, can significantly improve the cycle stability and rate performance of batteries under high temperature and high pressure.

[0023] In one embodiment of this disclosure, the acrylic monomers include one or more of acrylic acid, methacrylic acid, methyl acrylate, n-butyl acrylate, methyl methacrylate, and benzyl methacrylate; the fluorinated acrylic monomers include one or more of trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate, and hexafluorobutyl methacrylate. In the above embodiments, compared to homopolymers with single properties, copolymers synthesized from acrylic monomers and fluorinated acrylic monomers can more flexibly adjust their weak acidity, electronegativity, and hydrophobicity, making the copolymers more readily react with lithium residues on the surface of the cathode material, thereby reducing the amount of lithium residues and fluorinated derivatives and improving the stability of the layered structure of the high-nickel ternary material.

[0024] In one embodiment of this disclosure, the copolymer exists in the form of copolymer particles; the chemical formula of the high-nickel ternary cathode material is shown in formula (I): LiNi x Co y M z O2(I), where 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M includes Mn and Al.

[0025] A second aspect of this disclosure provides a method for preparing the modified high-nickel ternary cathode material described in the first aspect of this disclosure, the method comprising the following steps:

[0026] (1) Acrylic monomers and fluorinated acrylic monomers are copolymerized in the presence of an initiator and a first solvent to obtain a first material; a precipitant is added to the first material to obtain copolymer particles;

[0027] (2) Mix and stir the copolymer particles, high-nickel ternary cathode material and second solvent, and spray dry the resulting second material.

[0028] The method disclosed herein significantly reduces the amount of residual lithium compounds and fluorinated derivatives by coating a high-nickel ternary cathode material with a fluorinated copolymer that has weak acidity and hydrophobicity. This prevents the cathode material from reacting with residual lithium compounds and inhibits the contact between fluorinated derivatives and water and the surface of the cathode material. This isolates the highly reactive cathode material from the electrolyte, providing physical protection and thereby improving the stability of the layered structure of the cathode material.

[0029] In one embodiment of this disclosure, in step (1), the molar ratio of the acrylic monomer to the fluorinated acrylic monomer is (0.05-3):1, preferably (0.2-0.6):1; based on the weight of the first solvent, the total content of the acrylic monomer and the fluorinated acrylic monomer is 15-50% by weight. In the above embodiment, by selecting the preferred ratio of acrylic monomer and fluorinated acrylic monomer, it is beneficial to coat the surface of the cathode material with copolymer and obtain a copolymer coating layer of suitable thickness, thereby improving the coating effect on the high-nickel ternary cathode material.

[0030] In one embodiment of this disclosure, in step (1), based on the weight of the first solvent, the content of the initiator is 0.01–4% by weight, preferably 0.01–1% by weight; the volume ratio of the first material to the precipitant is (0.01–2):1, preferably (0.05–1):1; the temperature of the copolymerization reaction is 70–90°C, and the time is 0.5–10 h. In the above embodiment, by selecting an initiator with a preferred content, the chain length of the copolymer and the rate of the copolymerization reaction can be controlled, which is beneficial to obtaining a copolymer with a suitable molecular weight; by selecting a precipitant with a preferred volume, the copolymer in the first material can be precipitated, which is convenient for collection; and by selecting preferred copolymerization reaction conditions, it is beneficial to obtain a copolymer with a suitable structure.

[0031] In one embodiment of this disclosure, the initiator includes one or more of peroxide initiators, azo initiators, and redox initiators; in a preferred embodiment, the initiator includes one or more of benzoyl tert-butyl peroxide, benzoyl peroxide, methyl ethyl ketone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, ammonium persulfate, and benzoyl oxide; the precipitant includes one or more of dimethyl diacetate oxime, 8-hydroxyquinoline, sodium tetraphenylborate, and methanol; the first solvent includes one or more of dioxane, isopropanol, acetone, chloroform, and propylene oxide; the second solvent includes one or more of dioxane, isopropanol, acetone, ethanol, and ethyl acetate. In the above embodiments, by selecting preferred types of initiators and precipitants, copolymers with suitable structures can be further obtained; by selecting preferred first and second solvents, the monomers and copolymers can be fully dissolved therein, avoiding precipitation due to insufficient dissolution.

[0032] In one embodiment of this disclosure, in step (2), the weight ratio of the copolymer particles to the high-nickel ternary cathode material is (0.01–40):100, preferably (1–30):100. In the above embodiment, by selecting the preferred weights of copolymer particles, high-nickel ternary cathode material, and second solvent, the copolymer particles can be uniformly coated on the surface of the high-nickel ternary cathode material, thereby obtaining a modified high-nickel ternary cathode material with a suitable coating thickness.

[0033] In one embodiment of this disclosure, step (2) includes the following conditions for spray drying: the second material is dried by passing it through a centrifugal spray dryer, wherein the inlet air temperature of the centrifugal spray dryer is 150–300°C, the outlet air temperature is 50–100°C, and the rotation speed of the spray disc is 10,000–20,000 r / min; wherein the solid content of the second material is 10–80%, preferably 40–60%. The solid content refers to the percentage by mass of the solid components in the second material. In the above embodiment, by selecting the preferred spray drying method, the moisture in the second material can be rapidly evaporated, avoiding particle agglomeration; selecting the preferred solid content is beneficial for improving the spray rate and drying efficiency.

[0034] This disclosure, in a third aspect, provides an application of the modified high-nickel ternary cathode material described in the first aspect of this disclosure in batteries. When used in batteries, the modified high-nickel ternary cathode material provided by this disclosure can significantly improve the cycle stability and rate performance of batteries under high temperature and high pressure.

[0035] The present disclosure will be further illustrated by the following examples, but the present disclosure is not limited thereto.

[0036] Unless otherwise specified, all raw materials used in the following embodiments are commercially available products.

[0037] In the following embodiments, the specific testing methods are as follows:

[0038] The thickness of the coating layer was measured using a transmission electron microscope, specifically a FEI Tecnai G-20 instrument.

[0039] The number-average molecular weight was determined using an automatic average molecular weight analyzer (freezing point depression method), instrument model JSR2002.

[0040] The test method for surface lithium residue was potentiometric titration, instrument model SL1-2DJ-4B;

[0041] The electrochemical cycling performance was tested using the Blue Electric Test System, instrument model CT3001A.

[0042] Example 1

[0043] (1) Place 50g of dioxane (first solvent) and 0.2231g of azobisisobutyronitrile (initiator) in a three-necked flask, dissolve them completely, and then add 1.479g of acrylic acid monomer and 13.5975g of trifluoroethyl methacrylate monomer. Heat the three-necked flask to 75℃ for copolymerization reaction for 2h to obtain 10mL of the first material. Slowly pour 200mL of cold methanol (precipitant) into the first material for precipitation for 1h. Collect the white precipitate at the bottom, wash it, and dry it in a vacuum drying oven at 50℃ for 24h to obtain acrylic acid-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 1656g / mol.

[0044] (2) Mix 0.1g of PAA-TFEMA copolymer particles with 10g of LiNi 0.8 Co 0.1 Mn 0.1 O2 (high-nickel ternary cathode material) was added to 10g of dioxane (second solvent) and stirred continuously for 2h. The solid content of the resulting second material was 50.25%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 10000r / min. Modified high-nickel ternary cathode material 1 with a PAA-TFEMA copolymer coating layer on the surface was obtained, and the thickness of the copolymer coating layer was 5nm.

[0045] Example 2

[0046] Same as Example 1, except that in step (2), the high-nickel ternary cathode material LiNi is used. 0.8 Co 0.1Mn 0.1 O2 replaced with the same weight of LiNi 0.8 Co 0.1 Al 0.1 O2 was used to replace the second solvent, dioxane, with the same weight of isopropanol to obtain a modified high-nickel ternary cathode material 2 with a PAA-TFEMA copolymer coating layer on its surface. The thickness of the copolymer coating layer was 8 nm.

[0047] Example 3

[0048] (1) Place 50g isopropanol (first solvent) and 0.0460g ammonium persulfate (initiator) in a three-necked flask, dissolve them completely, then add 2.1452g acrylic acid monomer and 13.5975g trifluoroethyl methacrylate monomer. Heat the three-necked flask to 75℃ for copolymerization reaction for 2h to obtain 30mL of the first material. Slowly pour 200mL of 8-hydroxyquinoline (precipitant) into the first material for precipitation for 2h. Collect the white precipitate at the bottom, wash it, and dry it in a vacuum drying oven at 50℃ for 24h to obtain acrylic acid-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 4968g / mol.

[0049] (2) Mix 0.2g of PAA-TFEMA copolymer particles with 10g of LiNi 0.9 Co 0.05 Mn 0.05 O2 (high-nickel ternary cathode material) was added to 10g of isopropanol (second solvent) and stirred continuously for 2h. The solid content of the resulting second material was 50.49%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 10000r / min. Modified high-nickel ternary cathode material 3 with a PAA-TFEMA copolymer coating layer on the surface was obtained, and the thickness of the copolymer coating layer was 10nm.

[0050] Example 4

[0051] (1) 60g isopropanol (first solvent) and 0.3603g azobisisobutyronitrile (initiator) were placed in a three-necked flask and dissolved completely. Then, 2.8832g acrylic acid monomer and 7.5610g trifluoroethyl methacrylate monomer were added. The three-necked flask was heated to 80℃ for copolymerization reaction. The reaction time was 2h, and 18mL of the first material was obtained. 300mL of 8-hydroxyquinoline (precipitant) was slowly poured into the first material for precipitation. The precipitation time was 4h. The white precipitate at the bottom was collected, washed, and dried in a vacuum drying oven at 50℃ for 24h to obtain acrylic acid-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 2484g / mol.

[0052] (2) Add 0.5g of PAA-TFEMA copolymer particles and 10g of LiNi 0.88 Co 0.06 Mn 0.06 O2 (high-nickel ternary cathode material) was added to 15g of acetone (second solvent) and stirred continuously for 2h. The solid content of the resulting second material was 41.17%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 250℃, an outlet air temperature of 100℃, and a spray disc rotation speed of 15000r / min. Modified high-nickel ternary cathode material 4 with a PAA-TFEMA copolymer coating layer on the surface was obtained, and the thickness of the copolymer coating layer was 12nm.

[0053] Example 5

[0054] (1) 60g isopropanol (first solvent) and 0.3603g azobisisobutyronitrile (initiator) were placed in a three-necked flask and dissolved completely. Then, 2.8832g acrylic acid monomer and 9.2610g trifluoroethyl methacrylate monomer were added. The three-necked flask was heated to 80℃ for copolymerization reaction. The reaction time was 2h, and 45mL of the first material was obtained. 300mL of 8-hydroxyquinoline (precipitant) was slowly poured into the first material for precipitation. The precipitation time was 5h. The white precipitate at the bottom was collected, washed, and dried in a vacuum drying oven at 50℃ for 24h to obtain acrylic acid-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 3600g / mol.

[0055] (2) Mix 0.05g of PAA-TFEMA copolymer particles with 10g of LiNi 0.75 Co 0.15 Mn 0.15O2 (high-nickel ternary cathode material) was added to 15g of acetone (second solvent) and stirred continuously for 2h. The solid content of the resulting second material was 40.12%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 150℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 20000r / min. Modified high-nickel ternary cathode material 5 with a PAA-TFEMA copolymer coating layer on the surface was obtained, and the thickness of the copolymer coating layer was 2nm.

[0056] Example 6

[0057] Same as Example 1, except that in step (1), the mass of added acrylic monomer is 0.5454 g, the mass of trifluoroethyl methacrylate monomer is 25.452 g, and acrylic-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 16000 g / mol and modified high-nickel ternary cathode material 6 with a PAA-TFEMA copolymer coating layer on the surface are obtained, and the thickness of the copolymer coating layer is 26 nm.

[0058] Example 7

[0059] Same as in Example 1, except that in step (2), the mass of the added copolymer particles is 1g, the mass of the high-nickel ternary cathode material is 20g, and a second material with a solid content of 67.74% and a modified high-nickel ternary cathode material 7 with a PAA-TFEMA copolymer coating layer on the surface are obtained, with the thickness of the copolymer coating layer being 1nm.

[0060] Example 8

[0061] Same as Example 1, except that in step (1), the mass of the initiator azobisisobutyronitrile added is 1.67325g, and acrylate-trifluoroethyl methacrylate (PAA-TFEMA) copolymer particles with a number average molecular weight of 20000g / mol and modified high-nickel ternary cathode material 8 with a PAA-TFEMA copolymer coating layer on the surface are obtained, and the thickness of the copolymer coating layer is 18nm.

[0062] Example 9

[0063] (1) Place 150g of chloroform (first solvent) and 0.0841g of methyl ethyl ketone peroxide (initiator) in a three-necked flask, dissolve them completely, then add 1.72178g of methacrylic acid monomer and 25.014g of hexafluorobutyl methacrylate monomer. Heat the three-necked flask to 80℃ for copolymerization reaction for 5h to obtain 80mL of the first material. Slowly pour 500mL of sodium tetraphenylborate (precipitant) into the first material for precipitation for 1h. Collect the white precipitate at the bottom, wash it, and dry it in a vacuum drying oven at 50℃ for 24h to obtain methacrylic acid-hexafluorobutyl methacrylate copolymer particles with a number average molecular weight of 14816g / mol.

[0064] (2) Mix 3g of methacrylic acid-hexafluorobutyl methacrylate copolymer particles with 20g of LiNi 0.8 Co 0.1 Mn 0.1 O2 (high-nickel ternary cathode material) was added to 20g of ethyl acetate (second solvent) and stirred continuously for 2h. The solid content of the resulting second material was 53.49%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 300℃, an outlet air temperature of 90℃, and a spray disc rotation speed of 18000r / min. Modified high-nickel ternary cathode material 9 with a methacrylic acid-hexafluorobutyl methacrylate copolymer coating layer on the surface was obtained, and the thickness of the copolymer coating layer was 18nm.

[0065] Comparative Example 1

[0066] Same as Example 1, except that in step (1), trifluoroethyl methacrylate monomer is replaced with the same weight of acrylic monomer to obtain polyacrylic acid particles with a number average molecular weight of 720 g / mol and a comparative high-nickel ternary cathode material 1 with a polyacrylic acid coating layer on the surface, the thickness of which is 20 nm.

[0067] Comparative Example 2

[0068] Same as Example 1, except that in step (1), the acrylic monomer is replaced with the same weight of trifluoroethyl methacrylate monomer to obtain poly(trifluoroethyl methacrylate) particles with a number average molecular weight of 1680 g / mol and a comparative high-nickel ternary cathode material 2 with a poly(trifluoroethyl methacrylate) coating layer on the surface, the thickness of which is 30 nm.

[0069] Comparative Example 3

[0070] Similar to Example 1, except that: 20g of dioxane (first solvent) and 0.08924g of azobisisobutyronitrile (initiator) were added to a three-necked flask, and after complete dissolution, 1.479g of acrylic acid monomer was added. The three-necked flask was heated to 75°C for copolymerization reaction for 2 hours, yielding a polyacrylic acid solution with a number average molecular weight of 1000g / mol; 30g of dioxane (first solvent) and 0.13386g of azobisisobutyronitrile (initiator) were added to a three-necked flask, and after complete dissolution, 13.5975g of trifluoroethyl methacrylate monomer was added. The three-necked flask was heated to 75°C for copolymerization reaction for 2 hours, yielding a polymethyl methacrylate solution with a number average molecular weight of 3000g / mol; the polyacrylic acid solution and the polymethyl methacrylate solution were mixed and dried to obtain a mixture. 0.1g of the mixture was then mixed with 10g of LiNi 0.8 Co 0.1 Mn 0.1 O2 was added to 10g of dioxane (second solvent) and stirred continuously for 2 hours. The solid content of the resulting second material was 50.25%. The second material was dried by a centrifugal spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 10000r / min. A comparative high-nickel ternary cathode material 3 with a polymer coating layer on the surface was obtained, and the thickness of the polymer coating layer was 18nm.

[0071] Comparative Example 4

[0072] 0.1g of trifluoroethyl methacrylate monomer (TFEMA) and 10g of LiNi 0.88 Co 0.06 Mn 0.06 O2 was added to 15g of acetone and stirred continuously for 2 hours. The resulting material was dried by a centrifugal spray dryer with an inlet air temperature of 250℃, an outlet air temperature of 100℃, and a spray disc rotation speed of 12000r / min. A comparative high-nickel ternary cathode material 4 with TFEMA coating was obtained, with a coating thickness of 15nm.

[0073] Comparative Example 5

[0074] Add 0.1g of niobium ammonium oxalate and 10g of LiNi 0.85 Co 0.1 Mn 0.05O2 was added to 10g of deionized water and stirred continuously for 2 hours. The resulting material was dried by a centrifugal spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 12000r / min. Then, it was placed in a tube furnace with oxygen supply for heat treatment at a temperature of 500℃ for 5 hours to obtain a comparative high-nickel ternary cathode material 5 with a surface coating of niobium ammonium oxalate and a coating thickness of 20nm.

[0075] Comparative Example 6

[0076] Add 0.1g magnesium oxide and 10g LiNi 0.8 Co 0.1 Mn 0.1 O2 was placed in 10g of deionized water and ball-milled for 0.5h. Then it was placed in a tube furnace with oxygen supply for heat treatment at 500℃ for 5h to obtain a comparative high-nickel ternary cathode material 6 with magnesium oxide coating on the surface and a coating thickness of 30nm.

[0077] Comparative Example 7

[0078] 0.1g polyaniline, 10g LiNi 0.8 Co 0.1 Mn 0.1 O2 was added to 10g of polyethylene glycol and stirred continuously for 2 hours. The resulting material was dried by a centrifugal spray dryer with an inlet air temperature of 200℃, an outlet air temperature of 80℃, and a spray disc rotation speed of 12000r / min. A comparative high-nickel ternary cathode material 7 with polyaniline coating was obtained, with a coating thickness of 16nm.

[0079] Test case

[0080] Electrochemical performance tests were conducted as follows: The modified high-nickel ternary cathode materials prepared in Examples 1-9 and the comparative high-nickel ternary cathode materials prepared in Comparative Examples 1-7 were mixed with conductive agent acetylene black and binder PVDF in a mass ratio of 90:5:5. NMP (N-methyl-pyrrolidone) was then added and mixed thoroughly to obtain a slurry of a certain viscosity. The slurry was uniformly coated onto aluminum foil and dried at 90°C for 2 hours. After complete drying, the foil was pressed into sheets using a tablet press. The pressed electrode sheets were then punched into circular electrode sheets with a diameter of 14 mm and dried in a vacuum drying oven at 120°C for 2 hours. In an argon-protected glove box, using a Celgard 2400 membrane as the separator and a lithium metal sheet as the negative electrode, 1 mol L... -1LiPF6 / EC+DEC+DMC (volume ratio 1:1:1) was used as the electrolyte to assemble R2032 button cells. The assembled cells were subjected to charge-discharge tests above the blue voltage test range, with a test voltage range of 2.7–4.5V. The discharge specific capacity at a 1.0C rate was tested at room temperature (25±1℃) and high temperature (60±1℃), and the cycle retention rate of the cells after 100 cycles at room temperature (25±1℃) was also tested. The test results are as follows:

[0081]

[0082]

[0083] Test results show that the modified high-nickel ternary cathode materials prepared using the preparation method of this disclosure in Examples 1-9 have less surface lithium residue. After 100 cycles at 25°C and 1.0C, the capacity retention rate is above 86%, and after 100 cycles at 60°C and 1.0C, the capacity retention rate is above 91%. This indicates that the copolymer coating layer on the surface of the modified cathode material reacts with the lithium residue, reducing the amount of lithium residue and fluorinated derivatives, stabilizing the layered structure of the cathode material, and enabling the cathode material to maintain excellent cycle stability and rate performance when used in batteries under high temperature and high pressure conditions. Comparative Examples 1-7, which did not use the preparation method of this disclosure, produced comparative high-nickel ternary cathode materials with more surface lithium residue, resulting in poorer capacity retention after 100 cycles at 60°C and 1.0C. Therefore, the modified high-nickel ternary cathode materials provided in Examples 1-9 of this disclosure have superior performance compared to those provided in Comparative Examples 1-7.

[0084] The preferred embodiments of this disclosure have been described in detail above with reference to the accompanying drawings. However, this disclosure is not limited to the specific details of the above embodiments. Within the scope of the technical concept of this disclosure, various simple modifications can be made to the technical solutions of this disclosure, and these simple modifications all fall within the protection scope of this disclosure.

[0085] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, this disclosure will not describe the various possible combinations separately.

[0086] Furthermore, various different embodiments of this disclosure can be combined in any way, as long as they do not violate the spirit of this disclosure, they should also be regarded as the content disclosed in this disclosure.

Claims

1. A modified high-nickel ternary cathode material, characterized in that, The modified high-nickel ternary cathode material includes a high-nickel ternary cathode material and a copolymer coating layer covering the surface of the high-nickel ternary cathode material. The copolymer coating layer is formed by copolymerization of acrylic monomers and fluorinated acrylic monomers. The molar ratio of the acrylic monomers to the fluorinated acrylic monomers is (0.2~0.6):

1. The number-average molecular weight of the copolymer in the copolymer coating layer is 1200~14816 g / mol, and the thickness of the copolymer coating layer is 2~20 nm; the copolymer exists in the form of copolymer particles; The acrylic monomers include acrylic acid and / or methacrylic acid, and the fluorinated acrylic monomers include one or more of trifluoroethyl methacrylate, 2,2,3,3,3-pentafluoropropyl acrylate and hexafluorobutyl methacrylate.

2. The modified high-nickel ternary cathode material according to claim 1, characterized in that, The chemical formula of the high-nickel ternary cathode material is shown in formula (I): LiNi x Co y M z O2(I), where 0.5≤x≤0.95, 0≤y≤0.5, 0≤z≤0.5, x+y+z=1, and M contains Mn and Al.

3. A method for preparing the modified high-nickel ternary cathode material according to claim 1 or 2, characterized in that, The method includes the following steps: (1) Acrylic monomers and fluorinated acrylic monomers are copolymerized in the presence of an initiator and a first solvent to obtain a first material; a precipitant is added to the first material to obtain copolymer particles; (2) Mix and stir the copolymer particles, high-nickel ternary cathode material and the second solvent, and spray dry the resulting second material.

4. The method according to claim 3, characterized in that, In step (1), based on the weight of the first solvent, the total content of the acrylic monomer and the fluorinated acrylic monomer is 15-50% by weight.

5. The method according to claim 3, characterized in that, In step (1), based on the weight of the first solvent, the content of the initiator is 0.01~4% by weight; the volume ratio of the first material to the precipitant is (0.01~2):1; the temperature of the copolymerization reaction is 70~90℃ and the time is 0.5~10h.

6. The method according to claim 3, characterized in that, The initiator includes one or more of peroxide initiators, azo initiators, and redox initiators; The precipitant includes one or more of dimethylglyoxime, 8-hydroxyquinoline, sodium tetraphenylborate, and methanol; The first solvent includes one or more of dioxane, isopropanol, acetone, chloroform, and propylene oxide; the second solvent includes one or more of dioxane, isopropanol, acetone, ethanol, and ethyl acetate.

7. The method according to claim 6, characterized in that, The initiator includes one or more of benzoyl tert-butyl peroxide, benzoyl peroxide, methyl ethyl ketone peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, ammonium persulfate, and benzoyl peroxide.

8. The method according to claim 3, characterized in that, In step (2), the weight ratio of the copolymer particles to the high-nickel ternary cathode material is (0.01~40):

100.

9. The method according to claim 3, characterized in that, In step (2), the conditions for spray drying include: drying the second material by passing it through a centrifugal spray dryer, wherein the inlet air temperature of the centrifugal spray dryer is 150~300℃, the outlet air temperature is 50~100℃, and the rotation speed of the spray disc is 10000~20000r / min; wherein the solid content of the second material is 10~80%.

10. The application of the modified high-nickel ternary cathode material according to claim 1 or 2 in batteries.

Citation Information

Patent Citations

  • Long-life lithium ion battery ternary positive electrode material, preparation method thereof and application

    CN110444752A

  • Lithium ion battery composite positive electrode material, preparation method thereof and lithium ion battery

    CN113380990A

  • Preparation method of porous electrode active material, porous electrode active material prepared by the method, porous electrode active material, electrode comprising the same and secondary battery

    KR1020160042622A